Dampak Fluktuasi Harga Beras, Bawang Merah, Cabai Terhadap Inflasi - Dwi Lestari, Amanda; Erlikasna, Elfira; C. Simbolon, Ridho; Breta, Irena; Daniyal, Muhammad (Hasanuddin University, 2024)
Rice, shallots, chilies are one of the main food commodities. The increase in commodity prices could cause an increase in inflation in West Java Province. The aim of the research is to identify the influence of commodity price fluctuations for rice, shallots and chilies on inflation in West Java Province. The data used is secondary monthly time series data from 2019 to 2013 sourced from BPS. The analysis and calculations used by researchers are Vector Autoregression (VAR) analysis. The results show that commodity price movements of rice and chilies have a positive effect on inflation and are statistically significant and shallots are a commodity that makes a significant contribution to inflation. The price of shallots has a significant impact in the short term on the inflation rate in West Java Province. To maintain price stability, the government needs to set a benchmark price for shallots in the market to avoid unreasonable price spikes and carry out market operations by selling onions directly to consumers at lower prices to stabilize prices in the market.